An electrochemical chiral sensor for tryptophan enantiomers based on reduced graphene oxide/1, 10-phenanthroline copper(ii) functional composites. Issue 74 (13th August 2015) - Gou, Hao; He, Jingxian; Mo, Zunli; Wei, Xiaojiao; Hu, Rere; Wang, Yawei
<x xml:space="preserve">Abstract</x> An electrochemical chiral sensor based on reduced graphene oxide (RGO) non-covalently functionalized with 1, 10-phenanthroline copper(ii) (PhenCu) complex has been developed for electrochemical discrimination of tryptophan (Trp) enantiomers.